Age Adjusted Comorbidity Risk Index Does Not Predict Outcomes in an Autologous Hematopoietic Stem Cell Transplant Population. (February 2022) - Barth, Dylan; Singleton, Michael; Monohan, Gregory; McClune, Brian; Adams, Val
The hematopoietic comorbidity risk index (HCT-CI) is a pre-transplant risk assessment tool used to prognosticate morbidity and mortality of patients undergoing allogeneic hematopoietic stem cell transplantation. Recently, the HCT-CI was updated to include an age component (HCT-CI-age). Although other studies have validated this tool in allogeneic stem cell transplant recipients, it has never been studied in an autologous transplant patient population. We retrospectively reviewed 181 patients who underwent their first autologous hematopoietic stem cell transplant. We aimed (1) to assess whether an HCT-CI score of 3 or greater is associated with greater mean transplant hospital days, greater total hospital days, or greater risk of intensive care unit (ICU) utilization and (2) whether age influences any of these responses independent of HCT-CI. There were 136 patients with an HCT-CI score of 3 or higher and 45 with a score less than 3. The length of initial transplant hospitalization in days was not statistically significant (15.6 v 16.4 days, P = 0.38). Utilizing spline modeling prediction curves, transplant hospital days were estimated to increase from a mean of 15.5 days for a patient with 4 comorbidities to a mean of 22.7 days for a patient with 8 comorbidities. Age made no significant impact on any of the outcomes. The HCT-CI, with or without age, in an autologous stem cell transplantation did not predict length of hospitalization or utilization of the ICU. Patients with higher-HCT-CI scores at baseline may incrementally utilize more resources, and this should be explored in a larger cohort population.